Contestable Markets and the Theory of Industry Structure: AlReview Articleo - Spence, Michael (Journal of Economic Literature, 2016)
PHE NEW BOOK by William J. Baumol, John C. Panzar and Robert D. Willig is the culmination of several years of research on the related problems of understanding multiproduct cost structures and their implications for competition and market performance. It is a significant book for several reasons. The empirical reality that forms the starting point for the theoretical work is, I think, widely recognized to be important. Cost structures constitute one of the foundations of competitive strategy, and strongly influence industry structure. Notwithstanding this fact, the amount of microeconomic theory directed toward competitively relevant attributes of costs has been, if not minimal, then certainly more limited than the subject deserves. In fact, prior to the work of our authors, economists and business strategists did not have a language or a set of concepts with which to talk precisely about scale economies in a multiproduct setting. We now have at least the beginnings of such a language, and a body of theory that provides a grammar for using it. The theory of contestable markets was the subject of Baumol's presidential address at the American Economic Association meetings in Washington in December 1981. Both the theory and its presentation have generated controversy, useful controversy I think, because it helps clarify issues that need attention. I shall have remarks to offer later in this review concerning the normative and descriptive relevance of the contestable markets hypothesis. My plan for this review is as follows. I begin by outlining some of the principal definitions and propositions of the theory. This outline should not be mistaken for a complete summary of the book. But the economist who has not yet read the book needs a reasonably detailed picture of the approach. Few of the propositions require long proofs: in fact once they are stated, the proofs are often simple exercises. Having outlined some of the principal concepts, I comment upon their usefulness for understanding markets. And finally, I conclude by suggesting some ways in which the general subject may be pursued from this point forward.